The general character, distribution and spatial structure amphipodae Caspian Sea - I. M. Israpov; A. A. Abdulmedzhidov; T. M. Dzhamalutdinova (Юг России: экология, развитие, 2015)
The general character of distribution amphipodae mainly depends from abilitus to reach a food peculiar to all amphipodae.